ADVERSE DRUG REACTIONS PATTERN IN OUTPATIENTS AND INPATIENTS OF A TERTIARY CARE HOSPITAL FROM NORTHERN INDIA - IMRAN, MOHAMMAD; BHARDWAJ, ANU; KHARE, NEERAJ; SINGH, ABHISHEK (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Aim: Adverse drug reaction (ADR) reporting and monitoring activities are of vital importance for patient safety. It is a predominant ubiquitous and preventable clinical issue. This study was conducted to assess the ADR reporting in various departments. Methods: Standard ADR reporting forms were filled up by healthcare workers for patients from January 2020 to December 2021 for different departments. The causality appraisal of the ADRs was finished utilizing WHO-UMC causality evaluation scale. Seriousness of the recognized ADRs was evaluated at various levels, going somewhere in the range of 1–7 utilizing altered Hartwig-Siegel Scale. Results: The frequency of ADRs was higher among females (60.4%) when contrasted with guys (39.6%). The causality appraisal of ADRs cases showed that 85.7% of ADRs were “likely” and 51.2% of patients were sorted as “moderate” on seriousness evaluation of ADRs. The further examination of ADRs cases showed that 36.4% of ADRs cases (79/217) were “medical admissions due to ADR” and 63.6% of ADRs cases (138/217) were “ADRs happened in hospitalized patients.” Conclusion: This study finds that ADRs are frequent in this health center showing emergency clinic and this study would give an understanding into the example of ADRs in a tertiary medical services place and may assist with expanding mindfulness for additional pharmacovigilance studies.